2012
DOI: 10.1177/0272989x12453501
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Patients Derogate Physicians Who Use a Computer-Based Diagnostic Support System?

Abstract: Negative perceptions of computerized decision aid use may not be a product of the need to seek external advice more generally but may instead be specific to the use of a nonhuman tool and may be associated with individual differences in locus of control. Together, these 3 studies may be used to guide education efforts for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 20 publications
2
59
1
Order By: Relevance
“…Instrumentality should influence perceptions of physicians' self-focused emotion, such that they seem more empty, while also increasing preference for physicians who are patient focused and attend to patients' emotions. Consistent with this prediction, patients notice how caring their physicians are to them (Epstein, 2006;Mercado et al, 2012), respond more favorably to physicians who express affect toward patients (Beck, Daughtridge, & Sloane, 2002), derogate physicians who use impersonal decision aids (Arkes, Shaffer, & Medow, 2007;Shaffer, Probst, Merkle, Arkes, & Medow, 2012), and trust physicians based on their patient-focused affective characteristics (Sims, Tsai, Koopman-Holm, Thomas, & Goldstein, 2014). Specifically with respect to different types of emotions, we predict that when physicians are more instrumental, people will perceive them to have less self-focused (but not patientfocused) emotions and will prefer physicians who have more patient-focused (but not self-focused) emotions.…”
mentioning
confidence: 95%
“…Instrumentality should influence perceptions of physicians' self-focused emotion, such that they seem more empty, while also increasing preference for physicians who are patient focused and attend to patients' emotions. Consistent with this prediction, patients notice how caring their physicians are to them (Epstein, 2006;Mercado et al, 2012), respond more favorably to physicians who express affect toward patients (Beck, Daughtridge, & Sloane, 2002), derogate physicians who use impersonal decision aids (Arkes, Shaffer, & Medow, 2007;Shaffer, Probst, Merkle, Arkes, & Medow, 2012), and trust physicians based on their patient-focused affective characteristics (Sims, Tsai, Koopman-Holm, Thomas, & Goldstein, 2014). Specifically with respect to different types of emotions, we predict that when physicians are more instrumental, people will perceive them to have less self-focused (but not patientfocused) emotions and will prefer physicians who have more patient-focused (but not self-focused) emotions.…”
mentioning
confidence: 95%
“…Previous studies have shown, for example, that patients have negative perceptions of the competence of physicians who utilize computerized clinical decision support tools. 40,41 Such perceptions may make both physicians and patients reluctant to use these tools. Our own work has also suggested that patients’ utilization of personalized prognostic information is limited by their lack of experience with using such information, a tendency to favor heuristic-over risk-based decision making strategies, and perceptions that model-derived risk information is less valuable than other types of evidence (e.g., emotions, recommendations of trusted physicians, personal narratives).…”
Section: Discussionmentioning
confidence: 99%
“…Research also started investigating DST’s social influence. A lab experiment shows that physicians are concerned patients would think less of them and their skills if they needed a tool to make medical decisions [37]; Poor concern for clinician needs: Clinicians often lack the motivation to use a DST [22, 40]. They see it as getting in their way and slowing them down.…”
Section: Related Workmentioning
confidence: 99%
“…Research also started investigating DST’s social influence. A lab experiment shows that physicians are concerned patients would think less of them and their skills if they needed a tool to make medical decisions [37];…”
Section: Related Workmentioning
confidence: 99%